Water Quality Assessment for Qaladze Water Treatment Plant, Sulaymaniyah Governorate, Kurdistan Region, Iraq - Araz Hamza; Burhan Hama; Marif Karim; Kaywan Ahmed (Advances in Civil Engineering and Environmental Science, 2024)
This study assesses the water quality of the Qaladze water treatment plant, the drinking water source for the Qaladze city, Kurdistan region, Iraq which draws from the Little Zab River. A total of 50 water samples were collected monthly from January to December 2023. The methodology involved measuring physical parameters such as pH, alkalinity, conductivity, total dissolved solids (TDS), turbidity, and hardness against the standards set by the WHO and Iraqi drinking water regulations. Additionally, chemical parameters including chloride, calcium, sodium, potassium, magnesium, alkalinity, sulfate, and nitrate were analyzed. The results showed that the physical parameters met the established limits. Most chemical parameters consistently fell below the standards, with calcium exhibiting notable fluctuations exceeding the previous Iraqi standard of 50 mg/l during April, May, June, and September. Average values remained within acceptable ranges despite these variations. Maximum concentrations of TDS, chloride, conductivity, and nitrate were recorded from July to December, while minimum values were noted between March and September. Overall, the findings indicate that the water is safe and suitable for drinking and household use, with a water quality index of 49.94, classified as good. In adherence to earlier Iraq standards which was (50 mg/l), notable fluctuations observed, particularly in April, May, June, and September, are 56.60, 51.25, 53.75, and 53 respectively.